B-Complex Vitamins Sources, Intakes and Novel Applications - Guy LeBlanc, Jean (IntechOpen, 2022)
This book provides the most current information on the effects of vitamin B deficiency as well as the roles of niacin (vitamin B3), pyridoxine (vitamin B6), folate (vitamin B9), and vitamin B12 in numerous disorders. Chapters discuss novel applications of B-complex vitamins, such as thiamin in patients with critical conditions, dietary supplements in the prevention of renal stones, and treatment of COVID-19. Throughout, the authors discuss the effects of vitamin B deficiency from retrospective, perspective, and prospective points of view.